2021
DOI: 10.3892/ol.2021.13031
|View full text |Cite
|
Sign up to set email alerts
|

Cross‑link between ferroptosis and nasopharyngeal carcinoma: New approach to radiotherapy sensitization (Review)

Abstract: Ferroptosis is a recently discovered special type of regulated cell death that is strongly associated with both homeostasis maintenance and cancer development. Previous studies have indicated that a number of small-molecular agents inducing ferroptosis have great potential in the treatment of different types of cancer, including breast, pancreatic, prostate and head and neck cancer. However, the role of ferroptosis in nasopharyngeal carcinoma (NPC) has remained to be fully determined. To the best of our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 122 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…In addition, radiotherapy is the Frontiers in Genetics frontiersin.org main effective treatment modality in NPC, which is different from many solid tumors that require surgery. The cross-link between ferroptosis and radio-sensitization of NPC are generally being studied, hoping that linking the mechanism of ferroptosis with radiotherapy strategies could accelerate the development of novel ferroptosis-based treatment in NPC (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, radiotherapy is the Frontiers in Genetics frontiersin.org main effective treatment modality in NPC, which is different from many solid tumors that require surgery. The cross-link between ferroptosis and radio-sensitization of NPC are generally being studied, hoping that linking the mechanism of ferroptosis with radiotherapy strategies could accelerate the development of novel ferroptosis-based treatment in NPC (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to apoptosis, necrosis, pyroptosis, and autophagy, ferroptosis is a novel type of programmed cell death that is characterized by iron overload, lipid peroxidation, and the buildup of reactive oxygen species. It can be triggered by exogenous small molecule substances such as RSL3, sorafenib, sulfasalazine and so on, and can be reversed by ferroptosis inhibitors [3,4] . Cisplatin (DDP) is one of the standard chemotherapy drugs for the treatment of nasopharyngeal carcinoma [5] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Li et al discovered that the radiosensitivity of NPC could be promoted by targeting ferroptosis. [ 9 ] Hence, agents effective against ferroptosis might make great sense for NPC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Emerging evidence has pointed out that ferroptosis might be a promising target for cancer therapy, including NPC. [9] Xu et al found that itraconazole could relieve the stemness of NPC cells by inducing ferroptosis. [10] Li et al discovered that the radiosensitivity of NPC could be promoted by targeting ferroptosis.…”
mentioning
confidence: 99%